STRATEGI KEPEMIMPINAN KEPALA SEKOLAH BERJIWA WIRAUSAHA - Suyitno (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
The aims of this study is to describe and explain: (1) school promotion strategy; (2) education and training provision strategy; and (3) graduate marketing and alumni coordination strategy.This study uses a qualitative approach under a multiple case study design. The results of the study show that:(1) school promotion strategy to maintain branding, introduce school, and anticipate changes in government policy; (2) education and training strategy, which consists of strategies related to curriculum and learning materials, such as enterprise, religious content and field-based competency (IT); learning in Production Unit; industrial internship programs; National Exam success strategy; strategy in building up students’ characters (disciplined, morality, and attitude); coaching teachers based on reward and punishment, sincerity, and performance assessment; and (3) graduate marketing and alumni coordination strategy conducted since the students are in class XII through the collection of students’ biodata, curriculum vitaes, and questionnaires, and continued until the students graduates through short message gateway, facebook, email, mailing lists, and direct data collection. Graduate marketings is performed with a target time (expired in 3 months) by leveraging relationships with industrial and business world, empowering organizational networks, as well as the empowerment of alumni.